Fatigue and Long-Term Deformation Performance of Conventional and Rubber-Modified Bitumen - Idris, M.M. (Springer, 2020)
The intention of road pavement is to provide a convenient top surface for vehicles so that they can easily move without any difficulties, and safely from one place to another. The flexible pavement using conventional bitumen usually shows defects such as rutting, cracking, and fatigue failure, thus causing damage to roads earlier than the expected time. Therefore, an approach to bitumen modification using rubber has been done, so that it is more resistant to any deterioration of the pavement performance. An integration of natural rubber and bituminous materials is a tremendous innovation in world road pavement. Generally, natural rubber has high tensile strength and it is resistant to fatigue due to its elastic substance which is known as its feature. This modification is able to give an encouraging effect to the resilience of the road compared to the conventional bitumen, which has a limitation toward traffic loading. A consolidation of 6 of natural rubber to the 60/70 grade penetration of bitumen has shown an improvement to its main property. As we know, conventional bitumen susceptibility is directly proportional to the increasing of the traffic loading. With this alteration using a chemical composition in conventional bitumen is expected to prolong the lifespan of road pavement. The behavior of the modifier (natural rubber) has been observed by inclusive laboratory testing and appraisal. Â© Springer Nature Singapore Pte Ltd 2020.